2017
DOI: 10.1038/s41467-017-01542-z
|View full text |Cite
|
Sign up to set email alerts
|

The vaccinia virus DNA polymerase structure provides insights into the mode of processivity factor binding

Abstract: Vaccinia virus (VACV), the prototype member of the Poxviridae, replicates in the cytoplasm of an infected cell. The catalytic subunit of the DNA polymerase E9 binds the heterodimeric processivity factor A20/D4 to form the functional polymerase holoenzyme. Here we present the crystal structure of full-length E9 at 2.7 Å resolution that permits identification of important poxvirus-specific structural insertions. One insertion in the palm domain interacts with C-terminal residues of A20 and thus serves as the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 67 publications
5
75
0
Order By: Relevance
“…Some of this research work explores the pathophysiology of the disease [49] , [50] , [51] and the potential ways for improving its prevention or treatment [52] , [53] . Research is also being conducted on poxvirus for improving or developing new vaccines against smallpox [54] , [55] , [56] and on viruses that cause haemorrhagic fever, particularly for the development of treatments [57] .…”
Section: Recent Achievements In Infectious Agents That Can Be Used Asmentioning
confidence: 99%
“…Some of this research work explores the pathophysiology of the disease [49] , [50] , [51] and the potential ways for improving its prevention or treatment [52] , [53] . Research is also being conducted on poxvirus for improving or developing new vaccines against smallpox [54] , [55] , [56] and on viruses that cause haemorrhagic fever, particularly for the development of treatments [57] .…”
Section: Recent Achievements In Infectious Agents That Can Be Used Asmentioning
confidence: 99%
“…More recently, we were successful in solving the crystal structure of the catalytic subunit of the VACV DNA polymerase ([ 71 ], Figure 4 B). The structure allowed us to delineate E9-specific inserts, and to position the enzyme in a global model of the DNA polymerase holoenzyme.…”
Section: Antiviralsmentioning
confidence: 99%
“…The structure allowed us to delineate E9-specific inserts, and to position the enzyme in a global model of the DNA polymerase holoenzyme. We showed that an insertion within the palm domain binds to A20, and represents a mode of processivity factor binding that differs from other members of family B polymerases [ 71 ]. As mentioned above, E9 is the target of CDV and its derivative CMX001, and also other inhibitors, such as aphidicolin, phosphonoacetic acid, and cytosine arabinoside.…”
Section: Antiviralsmentioning
confidence: 99%
See 2 more Smart Citations